An Exceedingly Rare Case of Liraglutide-Induced Liver Injury - Swetha Parvataneni; Rajarajeshwari Ramachandran; Eric Then; Tyler Grantham; Vinaya Gaduputi (Case Reports in Gastrointestinal Medicine)
Liraglutide is a glucagon-like peptide-1 (GLP-1) receptor agonist used for the treatment of type 2 diabetes mellitus. We are reporting the second case of liraglutide-induced liver injury, with complete resolution of liver injury after discontinuation of the drug.